2021
DOI: 10.1002/admi.202100584
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Zero Thermal Expansion Ba1−xSrxZn2Si2O7‐Based Microwave Dielectric Ceramics for 3D Printed Dielectric Resonator Antenna with Integrative Lens

Abstract: High‐gain, low‐weight, wide bandwidth, and miniaturized lens antennas with stable properties against temperature are intensely required in extreme environments such as aerospace field. However, high‐performance microwave dielectric ceramics with near‐zero thermal expansion and frequency shift with temperature are very rare; moreover, the requirement of 3D printing processes also restricts their developments. Ba0.4Sr0.6Zn2Si2O7 with negative coefficient of thermal expansion (CTE), which originates from the stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 50 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…It should be noted that studies focused on the determination of CTE are mainly based on X‐ray diffraction (XRD) methods. [ 24–31 ] This method supposes placing the sample on a solid substrate. The violation of coherence at the film–substrate interface can lead to additional mechanical stresses that complicate the research conduction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that studies focused on the determination of CTE are mainly based on X‐ray diffraction (XRD) methods. [ 24–31 ] This method supposes placing the sample on a solid substrate. The violation of coherence at the film–substrate interface can lead to additional mechanical stresses that complicate the research conduction.…”
Section: Resultsmentioning
confidence: 99%
“…The obtaining of materials with a given CTE can be eased by the using of the size factor, which in the nanometer range often has a decisive influence on thermal expansion. For example, in works, [ 24–26 ] using the example of borides, it was shown that thermal expansion can both increase and decrease with the particle size of nanopowders. A similar situation is observed in continuous polycrystalline films.…”
Section: Introductionmentioning
confidence: 99%
“…ZrO 2 [276][277][278][279][280][281][282][283][284][285][286][287] [296] Heat exchanger/dissipation Al 2 O 3 [170], AlN [297][298][299] Tool with optimized design (inner cooling structure) Al 2 O 3 [180], cemented carbide [300] Optical application (lens, armored/ sensor window, etc.) Al 2 O 3 [301], MgAl 2 O 4 spinel [302], SiC [303], Nd-doped YAG [304], Yb-doped YAG [305] Antenna Al 2 O 3 +glass [306], Ba 1-x Sr x Zn 2 Si 2 O 7 [307], MgTiO 3 +CaTiO 3 [308] Nuclear fusion Li 2 TiO 3 [309], Li 2 SiO 3 [310] Table VIII waste. Thus, machines that work with a small amount of material (60 mL) [316] and studies about recycling raw materials [286,354] have emerged.…”
Section: Vat Photopolymerizationmentioning
confidence: 99%
“…Nevertheless, the rare negative thermal expansion (NTE) was observed in the BaMg 2 Al 6 Si 9 O 30 ceramic. The drastic changes in CTE from positive to negative can cause a mismatch in CTE in solids, which may result in serious problems for devices, such as permanent damage and cracking . The NTE in the BaMg 2 Al 6 Si 9 O 30 ceramic does not meet the requirements for practical applications and must be inhibited.…”
Section: Introductionmentioning
confidence: 99%